Pengaruh Variabel Ekonomi, Sosial, Dan Demografi Terhadap Jumlah Penduduk Miskin Pada Era Pasca Otonomi Daerah Di Provinsi Bali - Amira, Rizka; Marhaeni, Agung (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 3, No. 7, Juli 2014 (pp.282-336), 2014)
This study discuss about the number of poor in province of Bali in post- regional autonomy. Purpose of this study (1) is to analyze find out the effect in simultaneous, partial, and to know dominant variables of economic growth, level of education, unemployment, and population to the number of poor people in province of Bali in post-regional autonomy. The study was uses panel data with time series for 10 years and the cross- sectional of the data as much 9 districts/cities in province of Bali that resulted 90 observations. Data analysis technique was used to aks the problem is by multiple linear regression analysis model. The results showed that in imultaneous the economic growth, level of education, unemployment number, and population number have simultaneous effect toward the number of poor people in the province of Bali. Partial test of variables of economic growth and the level of education has significant negative effect toward the number of poor people in the province of Bali. This means that more high the economic growth and educational level achieved hence the number of poor people will be reduced. Variable of unemployment number and the number of people has significant positive effect toward the number of poor people in the province of Bali. This means that more high of number of unemployment number and the number of people hence the number of poor people will increase too. Variable of population number is dominan effect toward the number of poor in province of Bali.
Keywords: Poverty , Economic , Social